SARS-CoV-2 and Mycobacterium Fortuitum Coinfection: A Case Report - Tazegül Gül; Hatice Maraş; Özgür Demir; Ezgi Gülten; Güle Çınar; İrem Akdemir; Elif Mukime Sarıcaoğlu; Ebru Us; Mehmet Serhat Birengel (Ankara Üniversitesi Tıp Fakültesi Mecmuas, 2025)
Coronavirus disease-2019 (COVID-19) pandemic caused millions of people to become infected and had resulted several deaths. After initial resolution, in cases of clinical deterioration, it is essential to consider the possibility of coinfections. Non-tuberculousmycobacteria infections are rare and often overlooked. In this report, we present a severe acute respiratory syndrome-Coronavirus-2 and Mycobacterium fortuitum coinfected patient. Our intention is to bring attention to the possibility of such coinfection without a known history of any lung diseases or immunosuppression other than COVID-19 and thus, broadening the clinical thinking process of physicians.